Enhancing Li-ion battery efficiency: An experimental study on hybrid cooling approach with paraffin and forced air convection - Altuntop, Enis Selcuk; Erdemir, Dogan; Kaplan, Yuksel; Ozceyhan, Veysel (ELSEVIER, 2024)
This article experimentally investigates the application of commercial paraffin for the thermal management of Liion battery packs under various operational and design parameters. The performance of paraffin is compared to natural and forced air convection effects without paraffin. In the experiments, battery packs of 12 V, 24 V, and 48 V are utilized. The discharge rates are 1, 2, 3, 4, and 5C. The distance variations between the battery cells for the PCM cooling method are examined at 0.25D, 0.5D, and 1D (D is the diameter of the battery cell). The results indicate that the battery packs with natural air convection exceed the thermal limitations recommended by the battery cell manufacturer. Besides that, forced air convection created undesirable conditions for the long-term use of batteries. The energy efficiency values for hybrid cooling that combines paraffin and forced air are higher than those for forced air convection. The battery packs have demonstrated the best performance in 48 V, 0.5D and 0 m/s case with 97 % efficiency for 4C discharge rate. The lowest efficiency has been seen in 12 V, 0.5D and 0 m/s with 50 % for 5C discharge rate. The lowest temperature difference is observed in 12 V, 0.25D and 0 m/s for 1C discharge rate which is 1.9 degrees C. The highest temperature difference is spotted in 12 V, 0D, and 0 m/s case for 5C discharge rate which is 32 degrees C. The highest temperature is 102 degrees C in 48 V, 0D, and 0 m/s case for 5C discharge rate. The lowest temperature is 24 degrees C in 24 V, 0.5, and 7.5 m/s case for 1C discharge rate.
Keywords: Battery; Battery pack; Battery thermal management system (BTMS); Li-ion battery; Paraffin; Thermodynamics; Energy & Fuels; Engineering; Mechanics